The role of cohesive zone properties on intergranular to transgranular fracture transition in polycrystalline solids. (April 2017) - Lin, Liqiang; Wang, Xianqiao; Zeng, Xiaowei
A cohesive zone model is employed to simulate the fracture evolution and crack propagation in polycrystalline solids. Numerical simulations of fracture growth with various cohesive zone properties are presented and the simulation results capture the fracture transition from intergranular to transgranular mode. Three different random Voronoi grain cell tessellations are presented to study the grain size effects. The simulation results show that the intergranular to transgranular fracture transition in the polycrystalline solid is sensitive to key cohesive law parameters such as fracture energy and cohesive strength along grain boundaries and in grain cells. This study also provides evidence that tensile strength of polycrystalline solid increases as grain cell size decreases.